The international law of disaster relief - Caron, David D.; Kelly, Michael J.; Telesetky, Anastasia (New York : Cambridge University Press, 2014)
Disasters can strike often and with unexpected fury, resulting in devastating consequences for local populations that are insufficiently prepared and largely dependent upon foreign aid in the wake of such catastrophes. International law can play a significant role in recovery after natural disasters; however, without clear legal frameworks, aid may be stopped, delayed, or even hijacked - placing the intended recipients in critical condition. This edited volume brings together experts, emerging scholars, and practitioners from North America, Japan, New Zealand, and Australia to analyze the evolution of international disaster law as a field that encompasses new ideas about human rights, sovereignty, and technology. Chapters focus on specific natural disasters like Hurricane Katrina, Cyclone Nargis, and Typhoon Haiyan in addition to volcanic and earthquake activity, wildfires, and desertification. This book begins a dialogue on the profound implications of the evolution of international law as a tool for disaster response.
Machine generated contents note: Part I. The Legal Theory of International Disaster Relief: 1. International law and the disaster cycle Daniel A. Farber; 2. Natural disasters and the theory of international law Toshiya Ueki; 3. International disaster relief law and article 38(1)(c) of the statute of the international court of justice: the forgotten source of international law Imogen Saunders; 4. Evolution of international disaster response law: towards codification and progressive development of the law Emika Tokunaga; Part II. The Law of International Disaster Relief: From Local to Global: 5. International disaster response laws, rules, and principles: a pragmatic approach to strengthening international disaster response mechanisms Claire Clement; 6. Release of radioactive substances into the sea and international law: the Japanese experience in the course of nuclear disaster Yukari Takamura; 7. The international law of ninety-six hours: urban search and rescue teams and the current state of international disaster response law Kirsten Nakjavani Bookmiller; Part III. The Right of Access to International Disaster Relief: 8. Legal framework applicable to humanitarian actors responding to disasters in weak and fragile states Catherine Gribbin and Ilario Maiolo; 9. Disasters, despots, and gun-boat diplomacy Catherine Shanahan Renshaw; 10. Hunger without frontiers: the right to food and state obligations to migrants Katie Sykes; 11. Disasters, international law, and persons with disabilities Akiko Ito; Part IV. Disaster Prevention and Relief: Anticipatory Responses from State Actors: 12. Help from above: the role of international law in facilitating the use of outer space for disaster management Brian R. Israel; 13. Utilizing international climate-change-adaptation funding to reduce risks of natural disasters in the developing world Paul Govind; 14. Challenges to state sovereignty in the provision of international natural disaster relief Amelia Telec; Part V. Disaster Prevention and Relief: Anticipatory Responses from NGOs: 15. The role of international organizations in disaster response: a case study of recent earthquakes in Japan Kentaro Nishimoto; 16. International investment law and disasters: necessity, peoples, and the burden of (economic) emergencies Ibironke T. Odumosu-Ayanu; 17. Clarifying the acquis humanitaire: a transnational legal perspective on the internalization of humanitarian norms Dug Cubie.
Includes bibliographical references and index.
English.
Keywords: Disaster relief -- Law and legislation; Emergency management -- Law and legislation; LAW / International